Development of group counseling model with trait and factor approach to increase maturity of students career choices - Murisal Murisal; Neviyarni Neviyarni; Muri Yusuf; Mudjiran Mudjiran (International Conferences on Educational, Social Sciences and Technology)
This study is aimed to produce a model of a group counseling with trait and factor approach to improve the maturity of SMAN students’ career choices. Research design is research and development using quantitative and qualitative methods. Quantitative data are gathered based on field problems which is tested with validity test, effectiveness, and practicality. Meanwhile, qualitative data are collected by using observation, interview and focus group discussion. The research product is in the form as the group counseling model with trait and factor approach to improve the maturity of students’ career choices, counseling guidebook of trait and factor group for school counselors. Ultimately this model can be a prototype and standard in group counseling with a trait and factor approach to improving the maturity of students’ career choices.